A Vajdaság társadalmi-gazdasági helyzetének változásai és regionális sajátosságai napjainkban - Pál, Ágnes; Takács, Zoltán (Közép-Európai Közlemények, 2011)
This study is aimed at outlining the regional institutions and the possibilities for regional development (legal framework) in Voivodina. On the basis of earlier research into Serbian–Hungarian border zones, the aim of this current research is to describe briefly the level of the region’s social and economic development. The characteristics of its human resources, as well as the main features of the typical economic activities will be emphasised, with a special emphasis on agriculture and tourism, a significant part of the region’s service industry. These factors are also heavily dependent on global and European economic processes and the flow of working capital. The openness, the integration and cooperation between different actors of the economic life may benefit the overall process. In conclusion, the developmental possibilities will be surveyed, in relation to the region’s GDP and HDI indicators.